PROCESS OF OUTGASSING OF THE UPPER MANTLE OF THE EARTH - Azbel' I.Y.; Tolstikhin I.N. (My University, 1989)
New data on the solubilities of noble gases in basaltic melts and on their distribution between melt and restite, together with the idea that outgassing of the mantle results from the generation of oceanic lithosphere, the most powerful present-day igneous process, make it possible to propose a version of outgassing. Careful quantitative analysis of the processes indicates the possibility of reconciling the calculated and observed isotopic and elementary ratios of the noble gases with their concentrations in oceanic basalts, the amounts of gases in the atmosphere (allowing for rather vigorous early outgassing), and the ratios and concentrations of radioactive isotopes of the lithophile elements K, Rb and U in the oceanic and continental crust. The only assumption needed for this reconciliation is that the circulation of material of the oceanic lithosphere during past geological epochs, was about 2 to 3 times the present-day value. In the light of current geophysical data, this assumption appears quite acceptable.